2018
DOI: 10.1007/s11365-018-0529-0
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial intention among University students in Malaysia: integrating self-determination theory and the theory of planned behavior

Abstract: The present study endeavors to develop a deeper understanding of the motivational processes involved in intentional entrepreneurial behavior. For this purpose, it integrates the social cognitive approach of the theory of planned behavior (TPB) and the organismic theory of motivation of self-determination theory (SDT). More specifically, it tests the role of basic psychological needs of autonomy, competence and relatedness as defined in SDT in shaping university students' attitudes and intentions toward entrepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
170
3
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 186 publications
(220 citation statements)
references
References 73 publications
11
170
3
8
Order By: Relevance
“…A recent evidence found a strong support for the integration of SDT and TPB (Al-Jubari et al, 2018). In their study, it was found that the satisfaction of SDT constructs predicted EI of Malaysian university students via the mediating role of TPB factors.…”
Section: Self-determination Theorymentioning
confidence: 83%
See 3 more Smart Citations
“…A recent evidence found a strong support for the integration of SDT and TPB (Al-Jubari et al, 2018). In their study, it was found that the satisfaction of SDT constructs predicted EI of Malaysian university students via the mediating role of TPB factors.…”
Section: Self-determination Theorymentioning
confidence: 83%
“…Theoretically, the finding lends support to SDT and TPB integration, where the autonomous motivation is very much related to students' attitude, norms, and control perceptions. Students whose psychosocial needs are supported by the social environment would have favorable perceptions and inclination toward starting their own businesses, as choosing this career path reflects a sense of choice that emanates from their inner self (Al-Jubari et al, 2018). It is also revealed that they believe they are motivated by challenging task of entrepreneurship and they can effectively act upon it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CPEC provides several business opportunities for an individual in different sectors such as construction, property, and manufacturing industries (Maqsood, 2018;Raza et al, 2018;Tong, 2015). Scholars suggested that individual attitude will be changed by benefits, which subsequently create entrepreneurial intention (Al-Jubari, Hassan, & Liñán, 2018;Esfandiar et al, 2019;Gorgievski et al, 2018).…”
Section: Attitude Of Entrepreneur and Intentions Of Entrepreneurmentioning
confidence: 99%